Evaluation of stillbirths: an epidemiological study over a 10-year period in Senegal - Mbodji, Aissatou; Ndiaye, Mame Diarra; Diop, Daba; Ouattara, Doris F. E.; Sarr, Cherif C. T.; Wade, Mouhamadou; Ndour, Simon Birame; Gueye, Mamour; Mbaye, Magatte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The main objective of this study was to analyse a series of foetal deaths from an epidemiological, clinical and aetiological point of view. Methods: This study was performed over a period of ten (10) years, from 1 January 2014 to 31 December 2023. Our study included all patients who had delivered a stillbirth in our department after twenty-eight (28) weeks of amenorrhoea. The CODAC (causes of death and associated conditions) classification was then used to identify the principal aetiological groups. All data were analysed first in Microsoft Excel 2016 and then using the Statistical Package for Social Science (SPSS 26, Mac version). Results: Over 10 years, we recorded 1812 cases of stillbirth out of a total of 60794 deliveries, representing a frequency of 2.9%. The average age of the patients was 28 years, with a mean gestite of 1.97. Artificial induction of labour was performed in 20.9% of cases. The most common maternal pathologies were, in order of frequency, retroplacental haematoma, maternal obesity and gestational diabetes. A caesarean section was performed in 26.7% of cases. The average birth weight was 1916 g. Using the CODAC classification, the most common causes were maternal, followed by placental anomalies. No cause was found in 35.4% of cases. Conclusions: Our results reveal several challenges for improving the management of foetal deaths. It is crucial to strengthen diagnostic capacities, particularly through foetal autopsies and histological examinations of the placenta, and to train healthcare professionals in post-mortem investigation techniques.